2015
DOI: 10.1007/s00784-015-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

Response on: Comments on “Salivary 8-hydroxy-2-deoxyguanosine, malondialdehyde, vitamin C, and vitamin E in oral pre-cancer and cancer: diagnostic value and free radical mechanism of action”

Abstract: Dear Editor:In response to comment [1] on our published article [2], we would like to point out that cancer has indeed different pathways involving oxidative stress, hormonal factors, inflammation, and others. As such, cancer is considered a multi pathway disease, involving various diagnostic markers. In this way, salivary biomarkers may be multiple (8-hydroxy-2-deoxyguanosine, malondialdehyde (MDA), vitamin C, and vitamin E) but at the same time also present some further challenges to act as diagnostic biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…In agreement with our results (Kaur, Politis and Jacobs, 2016) reported that MDA levels were significantly higher in OSCC with sensitivity and specificity of 61% and 58% versus control. On comparing MDA of potentially malignant lesion versus control, both sensitivity and specificity were 55% while on comparing OSCC and OPML it was only 43% and 45% for sensitivity and specificity respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results (Kaur, Politis and Jacobs, 2016) reported that MDA levels were significantly higher in OSCC with sensitivity and specificity of 61% and 58% versus control. On comparing MDA of potentially malignant lesion versus control, both sensitivity and specificity were 55% while on comparing OSCC and OPML it was only 43% and 45% for sensitivity and specificity respectively.…”
Section: Discussionsupporting
confidence: 93%
“…This power analysis used MD level as the primary outcome. The effect size (f = 0.34) for comparison between the five groups was calculated based upon the results of (Kaur, Politis and Jacobs, 2016). Using alpha (α) level of (5%) and Beta (β) level of (20%) i.e.…”
Section: Sample Size Calculationsmentioning
confidence: 99%